1998
DOI: 10.1046/j.1365-2842.1998.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of non‐axial versus axial loading of oral implants in the mandible of the dog

Abstract: The influence of axial and non-axial occlusal loads on the bone remodelling phenomena around oral implants in an animal experiment is simulated in a finite element analysis. The axial and non-axial loading conditions were introduced by inserting a bilaterally supported fixed partial prosthesis and a cantilever fixed partial prosthesis on two IMZ implants in the mandible of beagle dogs. Earlier quantitative and qualitative histological analyses revealed a statistically significant different remodelling response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 18 publications
8
76
0
5
Order By: Relevance
“…'[Insert figure 6 about here]' Barbier et al 67 found that the horizontal loading of a freestanding implant evoked the largest maximum stresses, although the magnitude of the applied horizontal load was five times smaller than that of the vertical load. Non-axial loading has often been related to marginal bone loss, failure of osseointegration, failure of the implant and/or the prosthetic components and if connected to natural teeth, failure of the cement seal on the natural tooth.…”
Section: '[Insert Figure 5 About Here]'mentioning
confidence: 99%
“…'[Insert figure 6 about here]' Barbier et al 67 found that the horizontal loading of a freestanding implant evoked the largest maximum stresses, although the magnitude of the applied horizontal load was five times smaller than that of the vertical load. Non-axial loading has often been related to marginal bone loss, failure of osseointegration, failure of the implant and/or the prosthetic components and if connected to natural teeth, failure of the cement seal on the natural tooth.…”
Section: '[Insert Figure 5 About Here]'mentioning
confidence: 99%
“…In contrast, when non axial loads were applied on the specimen, the highest microstrain values were found by the SG 4 (Fig 2) placed closest to the tip of load application, indicating that the amount of load transmitted to the bone/implant interface depends on the site where the load was applied (6)(7)(8)12). Therefore, the first work hypothesis was accepted.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, when the occlusal force is applied on different locations and in a direction that creates leverage, it may cause stresses on the bone adjacent to the implant (4). In vitro (6) and in vivo (7) studies have revealed the negative effect of the application of non-axial loads when compared with axial loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-axial loads generate distinctive stress in the ridge especially in the cortical bone. The main remodeling differences between axial and non-axial loading are affected mostly by the horizontal component of the resultant stresses [53]. Therefore, for realistic simulation, combined oblique loads (axial and non-axial) are generally used.…”
Section: Loading Conditionsmentioning
confidence: 99%